Deconversion, Sport, and Rehabilitative Hope - Shoemaker, Terry (Religions, 2019)
This article, based on qualitative interviews and ethnographic research, explores three types of on-the-ground rehabilitative hope supplied by sport for many post-evangelicals within the upper Bible Belt region traversing through the process of deconversion. First, sport is an often-cited space that is identified as broadening social networks, leading to initial questioning of inherited religiosity. Second, sport offers a level of amelioration of relational fissures caused by religious shifts away from evangelicalism. Last, this research indicates that post-evangelicals highly value spaces for discussions of social justice, and athletic activism offers symbolic solidarity. Thus, sport and deconversion can be intertwined for Southern post-evangelicals. In the end, I argue that the triangulation of deconversion, hope, and sport within a Southern context creates a way of understanding the changing Southern ethos and pathos demarcated by a shifting away from a conservative Protestantism historically dominant in the region.